Intra and extra regional openness: The role of 'trust' builders as Open Innovation Intermediaries - Igone Porto; Jose Ramón Otegi (European Regional Science Association (ERSA), 2014)
The role of intermediaries in innovation processes has been analyzed in the literature from a dual point of view of the firm's performances. Being considered actors involved in the knowledge diffusion and technology transfer, intermediaries are considered collaborators of small and large enterprises, as active members of industrial policy. Intermediaries are supposed to be capable of developing a variety of activities such as partners identifying, technology selection, supplier's election, or counsel in decisions making process. Besides this, the state of the art has deeply analyzed the role of public and private organizations as intermediaries, focusing on different perspectives of the innovation process. A diversity of names can be identified in the literature to refer to these intermediaries. However, the performance of these players is considered fuzzy, taking into account the potential they could achieve. In this research, a case study is proposed, where the figure of Agents of Proximity is presented. These agents perform voluntary work in developing projects of technological optimization of the firms they work with. Firstly, in order to improve the individual competitiveness of those firms. Secondly, knitting relationships between firms settle in the region they work in, in order to improve the competitiveness of the territory. These agents are people, the economic players have confidence in, mainly because of the careers these proximity actors have developed. This figure is contrasted in the region of Durango, in the Basque country (Spain). The county has a strong specialization in the metal-mechanical industry, with a high orientation towards the automotive market. The crisis has highly impacted on the region with job destruction and SMEs closures. This has generated a inter-territorial cooperation movement between inner existing players of the county: Productive subsystem, -where the value chain firms can be identified-, Knowledge Generation Subsystem ?where 2 vocational trainings, the technological center AZTERLAN, and the Automotive Intelligence Center, AIC, are located. And Institutional Subsystem, where public development agencies and associations that strengthen social capital and regional values are included.
Keywords: L14; L31; O14; O22; O32; 330; cooperation; intermediation; facilitation; competitiveness